2021
DOI: 10.3390/ph14060537
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation Strategies for Antibody-Free Quantitative Analysis of High Mobility Group Box 1 Protein

Abstract: Sickness behavior and fatigue are induced by cerebral mechanisms involving inflammatory cytokines. High mobility group box 1 (HMGB1) is an alarmin, and a potential key player in this process. Reliable quantification methods for total HMGB1 and its redox variants must be established in order to clearly understand how it functions. Current methods pose significant challenges due to interference from other plasma proteins and autoantibodies. We aimed to develop an antibody-free sample preparation method followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…They, therefore, set out to develop an antibody-free liquid chromatography coupled with a tandem mass spectrometry-based detection method for HMGB-1. In particular, Kvivik et al showed that, notwithstanding suboptimal recovery, the method developed enabled "the identification of several unique HMGB-1 peptides" [140] (p. 12). This accomplishment, in turn, has the potential to allow for "the measurement of different redox variants" in the future [140] (p. 12).…”
Section: Novel Insights Into Brain Cytokine Production and Actionmentioning
confidence: 99%
“…They, therefore, set out to develop an antibody-free liquid chromatography coupled with a tandem mass spectrometry-based detection method for HMGB-1. In particular, Kvivik et al showed that, notwithstanding suboptimal recovery, the method developed enabled "the identification of several unique HMGB-1 peptides" [140] (p. 12). This accomplishment, in turn, has the potential to allow for "the measurement of different redox variants" in the future [140] (p. 12).…”
Section: Novel Insights Into Brain Cytokine Production and Actionmentioning
confidence: 99%
“…Recently, an antibody-free sample preparation method followed by liquid chromatography joined with tandem mass spectrometry (LC-MS/MS) to measure HMGB1 in human plasma has been developed. The reversed-phase liquid chromatography separation of intact HMGB1 in diluted plasma produced a higher degree of HMGB1 purification than immunoaffinity extraction, which is useful for overcoming its low recovery in body fluids [ 32 ]. Currently, the analytical methods represent a compromise between isoform resolution (LC/MS) and ease of use with high throughput measurement of total HMGB1 (ELISA) with the possibility of reducing interference (PCA-ELISA).…”
Section: Introductionmentioning
confidence: 99%